The rise of the halal economy and the potential issues for research - Abd Rahman, Azmawani (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
From a commercial perspective, the halal economy naturally encompasses all sectors affected by the Muslim population’s adherence to Islamic values lifestyle and business practices, which, ultimately, have an impact on the market. The potential of the halal economy is significant, as it touches the lives of Muslims, who make up about 23.4% of the world population; the combined population of which is growing at twice the rate of the global population. The rise of the halal economy is astonishing, as the potential consumers of the halal economy are not only limited to Muslims, but also extend to those outside the Islamic faith who share similar values. The value-based needs that are driving the halal economy sectors include the need for pure and healthy food, fair and ethical trade, environmentally friendly, modest clothing, family-friendly travel, and animal welfare. In her presentation, Azmawani will give a brief overview of the different halal economy sectors and a snapshot on the market size of key sectors. She will also address issues related to the rise of the halal economy around the globe and its global market potential. Through the discussion of key drivers, opportunities, and challenges of the halal economy, her presentation will also include some analysis on the publication trends and the potential research issues within the area of halal products and services.